The Universities and University Colleges Act in Malaysia: History, Contexts and Development - Wan Chang Da (Kajian Malaysia, 2019)
In Malaysia, Akta Universiti dan Kolej Universiti (AUKU) is the main legislation that governs public universities. It was enacted in 1971 and amended six times that had profound implications for the development of higher education, particularly on the governance and autonomy of public universities. However, the days of AUKU are numbered as the current Government in its election manifesto has slated for the act to be revoked and abolished. This paper examines the historical and chronological development of AUKU, more specifically the socio-political economic situation at the time of enactment and each subsequent amendment. In addition, the article also explores thematic issues related to AUKU, namely academic freedom and autonomy as well as the control of the State and Government on public universities.